Differential effects of subchronic acrylonitrile exposure on hydrogen sulfide levels in rat blood, brain, and liver. Issue 2 (5th April 2022) - Yang, Bobo; Yin, Changsheng; Zhang, Yu; Xing, Guangwei; Wang, Suhua; Li, Fang; Aschner, Michael; Lu, Rongzhu
Abstract: Background: Hydrogen sulfide (H2 S), as the third gasotransmitter participates in both cellular physiological and pathological processes, including chemical-induced injuries. We recently reported acute acrylonitrile (AN) treatment inhibited endogenous H2 S biosynthesis pathway in rat and astrocyte models. However, there is still no evidence to address the correlation between endogenous H2 S and sub-chronic AN exposure. Objectives: This study aims to explore the modulatory effects of prolonged AN exposure on endogenous H2S levels and its biosynthetic enzymes in rat blood, brain and liver. Methods: A total of 50 male Sprague-Dawley rats were randomly divided into 5 groups, including the control group and AN-treated groups at dosages of 6.25, 12.5, 25 or 50 mg/kg. Rats received one exposure/day, 5 days/week, for 4 consecutive weeks. The rat bodyweight and brain/liver organ coefficient were detected, along with liver cytochrome P450 2E1(CYP2E1) expression. In addition, the H2S contents in rat serum and plasma, and in cerebral cortex and liver tissues were measured by methylene blue method. The expression of H2S-generating enzymes, including cystathionine β-synthase (CBS), cystathionine γ-lyase (CSE) and 3-mercaptopyruvate sulfurtransferase (3-MPST) was also measured with Western blot both in rat cerebral cortex and liver. Results: Subchronic exposure to AN significantly inhibited bodyweight-gain and increased the liver CYP2E1 expression compared with the control. In addition, AN significantly increased H2 S levels in rat plasma and serum, but not in liver. The endogenous H2 S level in rat cerebral cortex was also significantly increased upon AN treatment, when expression of the major H2 S-generating enzymes, CBS and 3-MPST were significantly enhanced. However, hepatic protein levels of CBS and CSE were significantly increased, whereas hepatic levels of 3-MPST were significantly decreased. Conclusion: This study showed that sub-chronic AN exposure increased endogenous H2S contents in rat blood and brain tissues, but not liver, which may be resulted from the distinct expression profile of H2 S-producing enzymes in response to AN. The blood H2 S contents may be applied as a potential novel biomarker for surveillance of chronically AN-exposed populations. Highlights: Subchronic intraperitoneal exposure to acrylonitrile increased H2 S content in rat blood and cerebral cortex, but not in liver. Distinct tissue expression profiles of H2 S-producing enzymes contribute to the acrylonitrile-induced differential effects on the H2 S level. Blood H2 S level may be a biomarker for subchronic exposure to acrylonitrile. Graphical Abstract: